Incorporating Financial Sector Risk Into Monetary Policy Models : Application to Chile - Luna, Leonardo (IMF Working Papers; Working Paper, 2011)
This paper builds a model of financial sector vulnerability and integrates it into a macroeconomic framework, typically used for monetary policy analysis. The main question to be answered with the integrated model is whether or not the central bank should include explicitly the financial stability indicator in its monetary policy (interest rate) reaction function. It is found in general, that including distance-to-default (dtd) of the banking system in the central bank reaction function reduces both inflation and output volatility. Moreover, the results are robust to different model calibrations: whenever exchange-rate pass-through is higher; financial vulnerability has a larger impact on the exchange rate, as well as on GDP (or the reverse, there is more effect of GDP on bank's equity - id est, what we call endogeneity), it is more efficient to include dtd in the reaction function.